Perilunar Luxation. Case Report - Yaniel Truffín Rodríguez; José Julio Requeiro Molina; Rafael Ezmandy Gámez Arregoitía; Osmany Pérez Martínez (Medisur)
Within the specter of injuries found in dorsal perilunar luxation or injuries of the bigger arch, the one belonging to bigger frequency reciprocates with the fracture luxation trasescafo dorsal perilunar. Much less frequent are the luxations that associate the big bone's fractures and those with displaced fractures of the pyramidal. Throughout the above, the case of a 19 year old patient is presented, that came to the emergency room of Gustavo Aldereguía Lima, Cienfuegos Hospital, after suffering a fall on his left hand with background of previous health. Great increase of volume in the left-handed wrist, acute pain in spite of immobilization and absolute functional impotence were verified. Manual reduction under general anesthesia of the perilunar luxation of the carpus was accomplished. By means of X-ray pictures of control, anteroposterior and lateral of the wrist, escafoides's fracture and its characteristics were verified. For the marked angulation and conminution of the fracture surgical open-cast treatment was decided, using the technique of Ruse, that was postpone to the tenth day from the initial lesion, when the wrist was less inflamed and the risks of complications were less. The patient was discharged of the consultation of orthopedics to the six months of operated showing functional acceptable results.